Laser system for an atomic gravimeter. - Chua, Alvin Zhen Tao. (2013)
For this Final Year Project (FYP), we built a laser system that is intended to cool 133Cs. An External Cavity Diode Laser (ECDL) was configured to emit at 852 nm. We then built a Lock-in Amplifier (LA) and a Proportional Integral (PI) controller to help lock the frequency of the laser to the desired frequencies. For the purpose of this FYP, this is the D2 transition line. We first discuss the mathamatics behind the Two Level Atom and give theoretical understanding behind the concept of laser cooling. The theoretical aspects of the Doppler Free Saturation Absorption Spectroscopy were then discussed. We then observed the Saturated Absorption Spectrum for 133Cs and attempted to arrive at the Doppler Free spectrum for the same transition line.